Implementasi Theory of Planned Behavior dalam Mendeteksi Minat dan Perilaku Fraud pada Sektor Publik (Studi pada Bagian Keuangan di SKPD se-Kota Probolinggo) - Amrullah, Muhammad Mukhlis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aimed to examine the effect of attitudes, subjective norms, behavioral control on behavioral intention as well as the effect of behavioral intention on the fraudulent behavior. This research was conducted at all government unit offices in the Municipality of Probolinggo which is called SKPD by using a questionnaire. Survey responses collected from a sample of 62 staffs in the financial section within SKPD represented by the chief financial officer and treasurer. Data analysis method used is multiple regression linear analysis with SPSS Statistics. The findings indicate that all of variables in the TPB, such as attitude, subjective norms and behavioral control has significant effect on behavioral intention to fraud. This study were also found significant effect of behavioral intention toward fraudulent behavior. The implications of this research were provide recommendation and consideration in analyzing the tendencies of fraud that can be performed by government staff. Moreover in establishing policies to prevent fraudulent behavior which can be done by everyone such in public sector organizations.Â Keywords: attitude, subjective norms, behavioral control, intention, fraudulent behavior, public sector, theory of planned behavior.